Static Stability Analysis of Mass Sensors Consisting of Hygro-Thermally Activated Graphene Sheets Using a Nonlocal Strain Gradient Theory - SELVAMANI, Rajendran; MAHAVEER SREEJAYAN, Madasamy; EBRAHIMI, Farzad (Engineering Transactions, 2020)
This paper develops a nonlocal strain gradient plate model for buckling analysis of graphene sheets under hygro-thermal environments with mass sensors. For a more accurate analysis of graphene sheets, the proposed theory contains two scale parameters related to the nonlocal and strain gradient effects. The graphene sheet is modeled via a two-variable shear deformation plate theory that does not need shear correction factors. Governing equations of a nonlocal strain gradient graphene sheet on the elastic substrate are derived via Hamilton’s principle. Galerkin’s method is implemented to solve the governing equations for different boundary conditions. Effects of different factors, such as moisture concentration rise, temperature rise, nonlocal parameter, length scale parameter, nanoparticle mass and geometrical parameters, on buckling characteristics of graphene sheets are examined and presented as dispersion graphs.